1979
DOI: 10.1002/pssb.2220950208
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering and phase transformations of TlGaSe2 and TlGaS2 under pressure

Abstract: Raman spectra of single crystals TlGaS2 and TlGaSe2 are investigated in equilibrium conditions at room temperature under various hydrostatic pressures up to 7.25 and 9.27 kbar, respectively. Phase transitions at about 5 kbar are shown to occur in both the single crystals. Mode parameters γi = (1/vi) (dvi/dP) are determined for most of the Raman bands observed. The different values of these parameters are used to find out which frequencies have to be assigned to interlayer vibrations. It is shown that Raman spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 9 publications
2
12
1
Order By: Relevance
“…At low temperatures, all phonon lines are clearly resolved, but at elevated temperatures some closely spaced Raman lines are not resolved in the unpolarized spectra because of temperature-induced broadening. The Raman spectra of TlGaSe 2 crystal in this work at ambient conditions are in good agreement with those of previous studies [4,17,18]. We analyzed in detail the temperature dependence of six distinctive Raman-active modes observed at T = 320 K with frequencies 18.0, 77.9, 130.7, 191.8, 228.0, and 275.7 cm -1 .…”
Section: Temperature Dependence Of Mode Frequenciessupporting
confidence: 79%
See 2 more Smart Citations
“…At low temperatures, all phonon lines are clearly resolved, but at elevated temperatures some closely spaced Raman lines are not resolved in the unpolarized spectra because of temperature-induced broadening. The Raman spectra of TlGaSe 2 crystal in this work at ambient conditions are in good agreement with those of previous studies [4,17,18]. We analyzed in detail the temperature dependence of six distinctive Raman-active modes observed at T = 320 K with frequencies 18.0, 77.9, 130.7, 191.8, 228.0, and 275.7 cm -1 .…”
Section: Temperature Dependence Of Mode Frequenciessupporting
confidence: 79%
“…The frequency shifts for Raman modes of TlGaSe 2 crystal were fitted by means of Eqs. (1)- (3) using the experimental values of γ and α(T ) for TlGaSe 2 [18,20] with A, ν 0 , ν 1 , and ν 2 as adjustable parameters, keeping the sum, ν 1 + ν 2 = ν 0 , a constant (energy conservation). For all modes, the agreement between the theoretical and experimental dependencies was found to be good.…”
Section: Temperature Dependence Of Mode Frequenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time in IR and RS spectra (according to [6] in I R and RS spectra there are no lines whose frequencies coincide) only 25 phonon bands are present. Measurements of RS spectra under hydrostatic pressure [9] showed that a primitive cell has two SU-142092 Troitsk, Moscow region, USSR. layers as only two modes have an anomalously large mode Griineisen parameter 1 1 avi vi ap y i = --.…”
Section: Introductionmentioning
confidence: 99%
“…A t present, information is available on the sequence of PT in TlGaSe, and TlInS, [13 t o 191 with temperature as well as in TlGaS, and TlGaSe, [20] with pressure. Despite the use of different procedures to study PT in TIGaSe, and TlInS, crystals, it is still impossible t o establish the mechanisms of structural transformations and the special structural features of low-temperature phases.…”
Section: Introductionmentioning
confidence: 99%